The Role of a Healthy Lifestyle in Enhancing Quality of Life: Effects of Flaxseed on Gastrointestinal Symptom Severity in Patients with Irritable Bowel Syndrome - Agnieszka Woźniacka; Tomasz Pulanecki; Jerzy Krzeszowiak; Aleksandra Ożga; Alicja Podolska; Patrycja Kolano; Julia Wątor; Barbara Boba; Barbara Chojnacka; Sylwia Bryksy (Quality in Sport)
Irritable bowel syndrome (IBS) is a chronic, relapsing and often life-long disorder. It is characterised by the presence of abdominal pain or discomfort, which may be associated with defaecation and/or accompanied by a change in bowel habit(Irritable Bowel Syndrome in Adults: Diagnosis and Management Clinical Guideline, 2008). The treatment options for IBS have included pharmacological symptomatic relief of symptoms such as pain, diarrhoea or constipation. Alternative therapies, such as cognitive behavioural therapy and gut-directed hypnotherapy, have been used with good results. Flaxseed or linseed (Linum usitatissimum L.) comes from the flax plant, an annual herb. The main importance of flaxseed is in the human nutrition sector because it is emerging as an important functional food ingredient thanks to the content of active compounds, pointed to provide health benefits (El-Salhy, 2012). This narrative review aims to assess the impact of the therapeutic benefits of linseed for people with IBS.